2002
DOI: 10.1002/crat.200290005
|View full text |Cite
|
Sign up to set email alerts
|

Study of transport properties co – evaporated lead telluride (PbTe) thin films

Abstract: Thin films of lead telluride (PbTe) of thicknesses ranging from 1000 Å to 2500 Å have been prepared by co-evaporation (three temperature) technique, onto precleaned amorphous glass substrates at various temperatures. The deposited samples were annealed and annealed samples were used for characterization. Resistivity of these samples was measured by four-probe technique as a function of thickness and temperature. Activation energy for charge transport have been evaluated and found in the range of 0.09 to 0.106 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
3
2
0
Order By: Relevance
“…The texture structure suggests that ͑200͒ is the preferred film growth orientation due to its low surface energy. This is consistent with the result of coevaporated PbTe thin films on glass substrates reported by Khairnar et al, 13 which showed that ͑200͒ diffraction peak intensity varied with film thickness and substrate temperature during deposition. Figure 2 shows the surface morphology of PbTe films on ͑a͒ a glass slide substrate and ͑b͒ a 400 nm SiO 2 coated Si substrate obtained by AFM.…”
Section: A Structural and Morphological Characterizationsupporting
confidence: 92%
“…The texture structure suggests that ͑200͒ is the preferred film growth orientation due to its low surface energy. This is consistent with the result of coevaporated PbTe thin films on glass substrates reported by Khairnar et al, 13 which showed that ͑200͒ diffraction peak intensity varied with film thickness and substrate temperature during deposition. Figure 2 shows the surface morphology of PbTe films on ͑a͒ a glass slide substrate and ͑b͒ a 400 nm SiO 2 coated Si substrate obtained by AFM.…”
Section: A Structural and Morphological Characterizationsupporting
confidence: 92%
“…The estimated lattice cell parameters for as-deposited and annealed films are given in Table 2. The computed lattice constant 'a' is in good agreement with the JCPDS (78-1905) value and with earlier investigations [7,8,10,11]. There is an increase in crystallite size and decrease in strain as well as dislocation density as annealing temperature increases.…”
Section: Structuresupporting
confidence: 84%
“…The observed d-spacing and hkl planes are given in Table 1, which are in good agreement with the JCPDS (78-1905) data corresponding to cubic PbTe, and earlier reports [7][8][9][10][11][12][13] conform the rock salt (NaCl) structure of the PbTe film. In the XRD pattern, a prominent diffraction peak at 27.52°, which corresponds to the (200) plane, indicates that the crystallites predominantly grow in this direction [7,[10][11][12]. Figure 1b and c depicts the X-ray diffractogram of annealed films in which the peaks are observed with greater intensity than the peaks observed in Fig.…”
Section: Structuresupporting
confidence: 84%
“…On the other hand, TE thin films did not achieve yet a large diffusion, but the possibility to obtain TE coatings represents an interesting alternative also for future miniaturized thermal-to-electrical conversion devices. Many deposition techniques have been applied to obtain TE thin films, including molecular beam epitaxy [7], thermal evaporation [8] and pulsed laser deposition (PLD) [9]. PLD represents a very attractive technique, since it allows the deposition of complex native nanostructured films with good stoichiometry.…”
Section: Introductionmentioning
confidence: 99%